RELIGIOUS DYNAMICS IN UZBEKISTAN: HISTORICAL ROOTS AND MODERN PROBLEMS (Ta'limning zamonaviy transformatsiyasi, 2024)
Religion in Uzbekistan reflects a complex tapestry of historical legacies and contemporary challenges. This paper explores the intricate interplay between religion, culture, and politics in Uzbekistan, focusing on its rich historical diversity, predominantly Islamic character, and the enduring impact of Soviet-era suppression on religious practices. Following independence in 1991, Uzbekistan experienced a revival of religious expression, albeit within a framework of government regulation aimed at preserving national unity and stability. Despite efforts to promote religious tolerance, tensions persist, underscored by occasional reports of discrimination against religious minorities and restrictions on religious freedoms. Through a nuanced analysis of religious dynamics, this paper aims to provide insights into the multifaceted nature of religion in Uzbekistan, highlighting its cultural significance, interfaith dynamics, and evolving role in shaping the country's socio-political landscape.